A survey of practice in the management of haemolysis, icterus and lipaemia in blood specimens in the United Kingdom and Republic of Ireland. (July 2022) - Costelloe, Seán J.; Rico Rios, Natividad; Goulding, Nicola; Mistry, Hema; Stretton, Adam; De la Salle, Barbara; Hepburn, Sophie; Thomas, Annette; Atherton, Jennifer; Cornes, Michael
Background: Haemolysis, icterus and lipaemia (HIL) are common interferants in laboratory medicine, potentially impacting patient care. This survey investigates HIL management in medical laboratories across the UK and Republic of Ireland (ROI). Methods: A survey was sent to members of key professional organisations for laboratory medicine in the UK and ROI. Questions related to the detection, monitoring, quality control, and management of HIL. Results: In total, responses from 124 laboratories were analysed, predominantly from England (52%) and ROI (36%). Most responses were from public hospitals with biochemistry services (90%), serving primary care (91%), inpatients (91%), and outpatients (89%). Most laboratories monitored H (98%), I (88%), and L (96%) using automated indices (93%), alone or in combination with visual inspection. Manufacturer-stated cut-offs were used by 83% and were applied to general chemistries in 79%, and immunoassays in 50%. Where HIL cut-offs are breached, 64% withheld results, while 96% reported interference to users. HIL were defined using numeric scales (70%) and ordinal scales (26%). HIL targets exist in 35% of laboratories, and 54% have attempted to reduce HIL. Internal Quality Control for HIL was lacking in 62% of laboratories, and just 18% of respondents have participated in External Quality Assurance. Laboratories agree manufacturers should: standardise HIL reporting (94%), ensure comparability between platforms (94%), and provide information on HIL cross-reactivity (99%). Respondents (99%) showed interest in evidence-based, standardised HIL cut-offs. Conclusions: Most respondents monitor HIL, although the wide variation in practice may differentially affect clinical care. Laboratories seem receptive to education and advice on HIL management.